Comparison of the Outcome of Gentamycin Lavage Versus Normal Saline Lavage for Axillary Dissection in Modified Radical Mastectomy - Nabila Salamat, Muhammad Asadullah Khawaja, Wajahat Amir (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the gentamycin lavage with normal saline lavage after axillary dissection in modified radical mastectomy in terms of mean postoperative wound drainage was the objective of this study. Material: This Randomized controlled trial was conducted at Department of Surgery, Jinnah Hospital Lahore form July, 2018 to June, 2019. Total 100 female patients with 30 to 60 years of age, who underwent modified radical mastectomy for breast cancer. The patients were divided into two groups; group A (operative wound washed with 500ml normal saline) and B (wound washed with 500ml of gentamycin solution (240mg) in addition to the 500ml of normal saline). Results: Mean age and BMI of patients were 49.60±5.83 vs. 49.50±6.723 years (p=0.937) and 27.02±2.90 vs. 27.12±3.33 kg/m2 (p=0.873), in group A and B, respectively. Mean wound drainage were 356.46 ± 59.11 vs. 317.42 ± 51.92 ml (p=0.001), in group A and B, respectively. Conclusions: Gentamycin lavage reduces the postoperative axillary wound drainage after modified radical mastectomy as compared to normal saline lavage. Keywords: Gentamycin Lavage; Axillary Dissection; Modified Radical Mastectomy